Biofouling of Spiral Wound Membrane Systems - Vrouwenvelder, Johannes (IWA Publishing, 2011)
Biofouling of Spiral Wound Membrane Systems gives a complete and comprehensive overview of all aspects of biofouling, bridging the gap between microbiology, hydraulics and membrane technology. High quality drinking water can be produced with membrane filtration processes like reverse osmosis (RO) and nanofiltration (NF). As the global demand for fresh clean water is increasing, these membrane technologies are increasingly important. Most past and present methods to control biofouling have not been very successful. An overview of several potential complementary approaches to solve biofouling is given and an integrated approach for biofouling control is proposed.